Essential role of the peroxiredoxin 4 in Procambarus clarkii antioxidant defense and immune responses. Issue 75 (April 2018) - Dai, Li-Shang; Yu, Xiao-Min; Abbas, Muhammad Nadeem; Li, Chang-Sheng; Chu, Sheng-Hui; Kausar, Saima; Wang, Tian-Tian
Abstract: Peroxiredoxin (Prx) family members play a key role in host defense against oxidative stress, and modulate immune responses following microbial infection. Here, we cloned and characterized Procambarus clarkii Prx4 (Peroxiredoxin 4) cDNA, a regulator of oxidative stress and its expression analysis upon lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (Poly I:C) infection. The cDNA fragment of PcPrx4 was 744 bp in length, encoding a putative protein of 248 amino acid residues. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed that the PcPrx4 was expressed in all the examined tissues, and it was highest in the hepatopancreas followed by the hemocytes and gill. The challenge with LPS and Poly I:C significantly up-regulated the expression of PcPrx4 in hepatopancreas, hemocytes and gill when compared with the control. Recombinant PcPrx4 protein was used to investigate the antioxidant function in vitro by mixed-function oxidase assay. The results demonstrated a dose-dependent inhibition of DNA damage by rPcPrx4 protein. Altogether, our results imply that PcPrx4 is implicated in defense against microbial pathogens and oxidants in P. clarkii . Highlights: Prx 4 from Procambarus clarkii was identified and characterized for the first time. Transcripts and expression levels of PcPrx4 in the hepatopancreas were detected after LPS and Poly I:C challenge. The antioxidant role of recombinant PcPrx4 protein (rPcPrx4) was investigated in vitro by mixed-function oxidase assay. The results demonstrated a dose-dependent inhibition of DNA damage by rPcPrx4.